Effect of rehabilitation on the quality of life of people with spinal cord injury - Granados Carrera, Julio César (2020)
Introduction. The rehabilitation of spinal injuries (LM) seeks the social reintegration of the affected people, and assesses their limitations according to the degree of disability. Objective. To determine the effect of a rehabilitation program on quality of life of people with spinal cord injury. Methods. An analytical, observational, prospective and longitudinal study. People with a diagnosis of complete and incomplete spinal cord lesion at the quadriplegic and paraplegic level, male and female, between 14 and 80 years old, of traumatic and non-traumatic etiology and evolution time of less than 10 years were selected. Results. 65 people were selected as census sample who were hospitalized in the period january-june 2017. The most frequent clinical characteristics were the ASIA A paraplegic level with 30,8%, traumatic etiology with 72,3% and a time of evolution greater than 3 years, in 40%. Initial and final quality of life of the physical and mental components were found to be significant (p=0,001), all scales of the physical and mental components of the quality of life at the beginning and end were also significant (p=0,001). Conclusions. An improvement of quality of life, in physical and mental components, were founded in people with spinal cord injury at the end of the rehabilitation. There were positive changes in the quality of life in the mental component at the paraplegic level and in nontraumatic etiology. Changes in quality of life in the physical component were also found in people with incomplete spinal cord injury ASIA C.